Quinoa as polymer in edible films with essential oil: Effects on rainbow trout fillets shelf life. Issue 12 (28th October 2019) - Alak, Gonca; Guler, Kubra; Ucar, Arzu; Parlak, Veysel; Kocaman, Esat Mahmut; Yanık, Telat; Atamanalp, Muhammed
Abstract: In this study, it is aimed to investigate the potential effects of the use of quinoa as a carrier polymer in the production of edible film and the importance of essential oils (with lemon and sage oil) with highly important biological activity as supportive in this coating material. The rainbow trout fillets were wrapped with the edible film which were produced for this trial. The treatment varations were as the first group 2% lemon oil + quinoa edible film, second group 2% sage oil + quinoa edible film and the third group quinoa edible film alone and the last group control (untreated). All groups' fillets were stored at refrigerator (4 ± 0.5°C) for 15 days then they were periodically examined for some microbiological (psychrotrophic, mesophilic, aerobic, lactic acid bacteria, Enterobacteriaceae, and Pseudomonas counts) and chemical parameters (lipid peroxidation [Thiobarbituric Acid Reactive Substrate], total volatile basic nitrogen, and pH). The difference between the control group and the application groups was found to be important for all examined quality parameters during the storage period ( p  < .05). Lemon oil + quinoa was the most effective in preventing lipid oxidation of rainbow trout fillets. However, sage oil + quinoa group has proven to stronger antimicrobial specifications. As a result, it was determined that the coating material prepared by adding lemon and sage essential oil to quinoa edible film had positive effects on quality and shelf life in rainbow trout fillets. Practical applications: An alternative to edible packaging of animal origin, plant materials are researched with functional properties to obtain new packaging's for the food industry, especially fisheries, and to develop healthy, environmental, and natural packaging materials instead of synthetic packaging.